Effect of Custom Foot Orthoses on Vertical Jump in Flat-Footed Basketball Players - Anggriani, Atika Febri; Utomo, Prasetyo Catur (Jurnal Keterapian Fisik, 2025)
Background: Basketball is popular in Indonesia, and vertical jump ability plays a significant role in performance in the game. Abnormal curvature of the legs can reduce jump outcomes. The use of custom foot orthoses can help address this condition. This study aims to determine the effect of custom foot orthoses on vertical jumps in flat-footed basketball players.  Methods: This study used a one-group pretest-posttest design with a population of 25 people and 23 respondents selected through purposive sampling. The vertical jump was evaluated using a vertical jump test conducted before and after one month of using foot orthoses. Data were analyzed using a Paired Sample T-test.  Results: The results of the statistical test showed a p value of <0.001 (p < 0.05), indicating a significant difference in the use of custom foot orthosis before and after the intervention.  Conclusion: There is an improvement in the vertical jump of basketball players with flat foot condition.  Custom foot orthoses are recommended for use to improve the vertical jump of basketball players with flatfoot conditions.